Exploring Teachers’ Perception on the Teaching of Multicultural-based Religious Education - Mahmud, Muchammad Eka (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Multicultural-based religious education becomes very important to be applied at schools as well as in society. It is because its present can be a solution of varied disintegration problems in our country. In addition, religious education should strengthen brotherhood among religious society. It means that all schools in Indonesia should provide space and high attention to religious education as well as arising the attitude of respecting each other, because without religion as basic element in life and involve it in conflicts is a contradictive problems based on the principle of religion itself. The objective of this research is to figure out the importance of development of Multicultural-based religious education, its implementation as well as forms developed at schools at SMPN 1 Samarinda and SMPN 1 Sangatta, East Kutai, East Kalimantan. Moreover, this is a qualitative research where it studies about natural phenomenon which rely on fact. In this case, the researcher uses semi-structured interview to capture the teachers’ of religious education subject perception. The result of the study shows that both teachers at SMPN 1 Samarinda and SMPN 1 Sangatta, East Kutai, agree that Multicultural-based religious education in very important to be applied in education, especially to the lower level such Junior High School. The shortage of the application of multicultural aspect in religious education is pointed out in this research as well as the future implication related to Indonesian curriculum.